Semiblind Channel Estimation for IFDMA in Case of Channels with Large Delay Spreads. (9th December 2010) - Sohl, Anja; Klein, Anja
Abstract : Discrete Fourier Transform- (DFT-) precoded Orthogonal Frequency Division Multiple Access (OFDMA) with interleaved subcarrier allocation per user is considered which is denoted as Interleaved Frequency Division Multiple Access (IFDMA). For IFDMA, the received signal exhibits a cyclostationarity with the parameterQ which defines the number of allocated subcarriers per user. In previous works, we have shown that this cyclostationarity can be exploited for the application of subspace-based semiblind channel estimation to IFDMA. Nevertheless, the formerly proposed algorithm is restricted to channels with small delay spreads, meaning that the number of channel delay taps needs to be smaller thanQ . In this paper, we introduce a new semiblind subspace-based channel estimation algorithm which identifies a subspace of the received signal that is spanned by theQ elements of the so-called cyclic channel impulse response. By doing so, the number of elements to be estimated is reduced and the proposed algorithm is able to cope with channels with large delay spreads.